2012
DOI: 10.1155/2012/175162
|View full text |Cite
|
Sign up to set email alerts
|

Mie Plasmons: Modes Volumes, Quality Factors, and Coupling Strengths (Purcell Factor) to a Dipolar Emitter

Abstract: Using either quasistatic approximation or exact Mie expansion, we characterize the localized surface plasmons supported by a metallic spherical nanoparticle. We estimate the quality factorQnand define the effective volumeVnof thenth mode in such a way that coupling strength with a neighbouring dipolar emitter is proportional to the ratioQn/Vn(Purcell factor). The role of Joule losses, far-field scattering, and mode confinement in the coupling mechanism is introduced and discussed with simple physical understan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…The normal modes of the system and their eigenfrequencies are computed using the formulas given by eqs. (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). It will be shown that even in the more symmetric situations, the Purcell factor has contributions from more than one normal mode.…”
Section: Purcell Factor Of Silicon Nano-cavitiesmentioning
confidence: 94%
See 3 more Smart Citations
“…The normal modes of the system and their eigenfrequencies are computed using the formulas given by eqs. (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). It will be shown that even in the more symmetric situations, the Purcell factor has contributions from more than one normal mode.…”
Section: Purcell Factor Of Silicon Nano-cavitiesmentioning
confidence: 94%
“…The reason stems from the definition of the normal modes of the systems given by eqs. (19)(20)(21)(22)(23)(24)(25)(26). In particular, the only dependence of E (x) j,mz,q in m z comes via Y jmz and χ mz , and it can be seen that an integral over 2π equalizes the behavior of the modes with m z and −m z .…”
Section: Effective Volumes Average Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, spectrally narrow emission at 530 nm from gold nanoparticles coated with dye-doped glass (OG-488 in silica) has been observed 35 but no independent determination of the material gain of the doped glass was provided. In general, the interaction between realistic gain materials and bright and dark plasmon modes of spherical metal nanoparticles 36 and more complex nanostructures 37,38 will certainly be an active topic of theoretical and experimental research in the coming years.…”
Section: Loss and Gain In Plasmonic Waveguides And Nanoparticle Spasersmentioning
confidence: 99%